Analysis of Marketing Strategies by Labstore in Attracting Consumer Purchase Interest in Student Products at UNPAM - Derizka Inva Jaswita; Syamsuddin, Rahmi Andini; Haidilia Maharani (International Journal of Educational and Life Sciences, 2024)
This study aims to evaluate the effectiveness of Labstore's current marketing strategy and identify the optimal approach to attract consumer interest in products created by Unpam students. This research employs a descriptive qualitative method, which involves describing phenomena or events as they occur. The findings of this study are as follows: First, regarding the product dimension, it is essential to focus on product quality, including durability, taste (for food and beverages), and packaging. Second, in terms of pricing, it is crucial to analyze competitors' prices for similar products to offer prices that are affordable to Labstore's primary consumers, who are mostly students. Third, the location and facilities of Labstore are generally considered good, with most participants finding Labstore a comfortable place to shop. Lastly, in the promotion dimension, the study suggests enhancing promotional efforts by adding cost-effective yet impactful media.